Outcomes and toxicities in oligometastatic patients treated with stereotactic body radiotherapy for adrenal gland metastases: A multi-institutional retrospective study. (March 2022) - Baydoun, A.; Chen, H.; Poon, I.; Badellino, S.; Dagan, R.; Erler, D.; Foote, M.C.; Louie, A.V.; Redmond, K.J.; Ricardi, U.; Sahgal, A.; Biswas, T.
Highlights: SBRT to adrenal gland oligometastases achieves a satisfactory local control and OS. A minimum PTV dose BED10 > 46 Gy was associated with an improved OS and LRFS. A prescribed BED10 > 70 Gy was correlated with improved local control. High adrenal metastases volume should not preclude the delivery of SBRT. Abstract: Background: Studies reporting SBRT outcomes in oligometastatic patients with adrenal gland metastases (AGM) are limited. Herein, we present a multi-institutional analysis of oligometastatic patients treated with SBRT for AGM. Material/methods: The Consortium for Oligometastases Research (CORE) is among the largest retrospective series of patients with oligometastases. Among CORE patients, those treated with SBRT for AGM were included. Clinical and dosimetric data were collected. Adrenal metastatic burden (AMB) was defined as the sum of all adrenal GTV if more than one oligometastases is present. Competing risk analysis was used to estimate actuarial cumulative local recurrence (LR) and widespread progression (WP). Kaplan-Meier method was used to report overall survival (OS), local recurrence-free survival (LRFS), and progression-free survival (PFS). Treatment related toxicities were also reported. Results: The analysis included 47 patients with 57 adrenal lesions. Median follow-up was 18.2 months. Median LRFS, PFS, and OS were 15.3, 5.3, and 19.1 months, respectively. A minimum PTV dose BED10 > 46 Gy was associated with an improved OS and LRFS. A prescribed BED10 > 70 Gy was an independent predictor of a lower LR probability. AMB>10 cc was an independent predictor of a lower risk for WP. Only one patient developed an acute Grade 3 toxicity consisting of abdominal pain. Conclusion: SBRT to AGM achieved a satisfactory local control and OS in oligometastatic patients. High minimum PTV dose and BED10 prescription doses were predictive of improved LR and OS, respectively. Prospective studies are needed to determine comprehensive criteria for patients SBRT eligibility and dosimetric planning.